Railway network of Galicia and Austrian Silesia (1847-1914) - Kaim, Dominik; Taczanowski, Jakub; Szwagrzyk, Marcin; Ostafin, Krzysztof (Journal of maps, 2020)
We describe and share reconstructed data of the historical railway network of Galicia and Austrian Silesia - two regions of the Habsburg Empire that covered more than 80 000 km 2 that are currently divided among Czechia, Poland and Ukraine. The network dataset includes the times of railway appearance and of the most dynamic development until 1914, which marked the outbreak of the First World War. Most of the lines were reconstructed based on OpenStreetMap data, and the lines, which were closed down between 1914 and 2019 and are no longer available in spatial datasets, were reconstructed based on high-resolution satellite imagery and historical maps. Altogether, the network dataset covers nearly 5000 km on 127 lines. The data are accompanied by a set of attributes, i.e. the year of construction, length, starting point, finish point, and type (normal, narrow-gauge, etc.), and are available for download in the shp format.